JENIS-JENIS BURUNG DI PERKEBUNAN SAWIT PT HUTAHAEAN KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - -, Agus (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
Research on diversity of bird in palm oil plantations PT Hutahaean Tambusai Rokan Hulu district of Riau have been conducted from November 2015 using survei methods, samples are identified directly in the field. Determination research station based on the by Purposive random sampling, technique with vegetation for station from results, the 8 families, 9 spesies with a total of 29 individu, namely Aegithinidae (Aegithina tiphia), Alcedinidae (Halcyon smyrnensis), Columbidae (Geopelia striata, Spilopelia chinensis), Phasianidae (Coturnix chinensis), Picidae (Dinopium javanense), Ploceidae (Passer montanus L), Pycnonotidae (Copsychus saularis), Sturnidae (Acridotheres cinereus). The bierdâs spesies dominate is Geopelia striata, Spilopelia chinereus (Columbidae). Index diversity is category medium, with value .1.9.